2004
DOI: 10.1177/13670069040080030701
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Irish skills: A longitudinal study of a school-acquired second language

Abstract: This paper describes a study of retention of school-acquired Irish among school leavers. The initial group selected represented final year secondary school students from three different instructional categories: ordinary level Irish, advanced level Irish and immersion school students. Participants were interviewed and their language skills assessed as they completed their study of Irish and again 18 months after they had left secondary school. Proficiency was measured in terms of scores on a communicative test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 11 publications
4
28
1
1
Order By: Relevance
“…9). Research on FL attrition often deals with languages which have been acquired to different levels of proficiency (research carried out by Murtagh & Van der Slik, 2004;Reetz-Kurashige, 1999). It is often very difficult (or impossible) to determine ultimate attainment (i.e.…”
Section: Methodological Issues and Constraints In Fl Attritionmentioning
confidence: 99%
“…9). Research on FL attrition often deals with languages which have been acquired to different levels of proficiency (research carried out by Murtagh & Van der Slik, 2004;Reetz-Kurashige, 1999). It is often very difficult (or impossible) to determine ultimate attainment (i.e.…”
Section: Methodological Issues and Constraints In Fl Attritionmentioning
confidence: 99%
“…Moreover, one study found no changes at all in performance, across proficiency levels, after either 2 or 4 years of limited exposure [22]. Finally, in some cases a gain in performance has been observed: after 1.5 years of limited exposure in one study, particularly for L2 learners with immersion as well as classroom training [24], and in another study after 2 years, though only for some abilities, such as listening and reading comprehension [18]. It remains unclear what might explain such gains, which have been attributed to motivation and to L2 experience during the period of ostensibly limited exposure [24], or to factors related to general maturation, cognitive development, or continued academic training [18].…”
Section: Introductionmentioning
confidence: 97%
“…Fourth, in all six previous studies subjects had at least some L2 exposure during the period of ostensibly limited exposure, and only two studies seem to have attempted to control for this factor [17], [18]. In fact, in at least one study in which gains were observed, the authors attributed these changes to L2 exposure during this period [24]. Thus it remains unclear to what extent any observed changes are due to the time lag or to continuing exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Rigorous investigations describing the nature of FL attrition have failed to demonstrate whether forgetting FL linguistics aspects is permanent but might in fact improve or recover after a period of no or limited use (Alharthi, 2012, Hedgcock, 1991Murtagh & der Slik, 2004Weltens & Grendel, 1993Weltens, 1989;Xu, 2010). While there seems to be a consensus that deterioration in skills or linguistic aspects is likely to occur as exposure to the FL ends, there is no widely accepted theory that accounts for the various manifestation of attrition.…”
Section: Introductionmentioning
confidence: 99%